Multi disciplinary approach in weight management: Experience in the Philippines - Eliza Mei Fransisco (Indonesian Nutrition Association, 2022)
Our Weight Management Centers are composed of a multidisciplinary team of medical specialists (Medical Nutrition, Endocrinology, Surgery, Rehab Medicine, Sleep Medicine, Bariatric Surgery) and allied professionals such as clinical dietitians, physical therapists, psychologists, and nurses. The multi-disciplinary and inter-disciplinary approach helps patients embark on lifestyle changes and succeed in overcoming obesity.